Loss of land and livelihoods from mining operations: A case in the Limpopo Province, South Africa. (December 2020) - Shackleton, Ross T.
Highlights: Loss of land from mining can negatively affect local livelihoods in rural underdeveloped areas. Decreased use of previsioning ecosystem services and access to natural resources are evident. Mining caused reductions in crop agriculture (fields), livestock grazing and use of non-timber forest products for affected households. This increases household venerability and adequate compensation or livelihood alternatives are needed to build resilience. Future policy on compensation should account for long-term losses, and the lack of alternative non-land based options for communities. Abstract: Loss or degradation of communal lands can have major implications for people's livelihoods and well-being in rural underdeveloped areas. Mining operations are one driver of land loss with negative implications for people. This study assesses the livelihood effects of open-cast mining on a rural communal land village that lost 8 000 ha of land and compares it to another village nearby that did not. The results suggest that the loss of land and the ecosystem services they provide has negatively affected people's livelihood strategies and outcomes. On average, only 23 % of households in the affected village had crop fields compared to an adjacent village, that did not lose land to the mine, where 90 % of households had a crop field. This accounts for substantial losses in income through agriculture, both as cash earnings and savings, and negatively affects household food security. As a result of the mine the affected community has also lost access to grazing, and now many households must pay to graze their livestock in other areas. Furthermore, the option to harvest several key natural resources (provisioning services) or non-timber forest products (NTFPs) such as wild fruits and vegetables, edible insects, fuelwood, and to a lesser extent resources like reeds and medicinal plants were lost due to the mine, negatively impacting local livelihoods. NTFPs are important for rural livelihoods as they allow for cash saving, income generation and act as a safety net or fall-back option during times of increased vulnerability. The findings also give a good indication of changes in agriculture and resource use over time and the varying reasons for this. Other negative effects from the mine included; cracking of houses due to blasting, dust pollution, water contamination, social and cultural effects, community alterations and conflicts, and very little was seen to be gained in terms of employment through Social Labour Plans (SLPs) or corporate social responsibility (CSR) initiatives. Households in the village affected by the mine lose approximately R 15 000 per year through losses of agricultural potential and the ability to collect NTFPs, which is larger than the annual cash incomes for most households. This value is likely to be an underestimate of the total value lost, as reductions in grazing potential and the loss of supporting, regulating and cultural ecosystem services were not included in this figure. This study highlights the importance of considering land access and associated land-based livelihoods in rural communal land areas in the context of disturbance and change. Recommendations for future assessments and policy on compensation for rural communities are made and issues relating to CSR are discussed.